The effect of bank failures on small business loans and income inequality - Contreras, Salvador; Ghosh, Amit; Hasan, Iftekhar (Journal of Banking & Finance, 2023)
Using variation in the timing and location of branches of failed banks we analyze its effect on income inequality. Employing a difference-in-differences specification we find that bank failures increased the GINI by 0.3 units (or 0.7%). We show that the rise in inequality is due to a decrease in the incomes of the poor that outpaces declines of the rest. We further show that individuals with lower levels of education exhibit a relatively greater decline in real wages and weekly hours worked. Exploring channels of transmission, we find income inequality is explained by a general decline in small business loans. This in turn reduces net new small business formation and their job creation capacity, a sector that hires a substantial share of low-income earners.